Pengaruh Konsep Tri Kaya Parisudha, Efektivitas Pengendalian Internal, Dan Moralitas Individu Pada Kecenderungan Kecurangan Akuntansi Di LPD Se-Kecamatan Kuta Selatan - Sinaga, I Putu Agra Sanjaya; Wati, Ni Wayan Alit Erlina; Ayu, Putu Cita (Hita Akuntansi dan Keuangan, 2025)
Accounting fraud is an intentional act with bad ethics that can harm an organization or company. This study aims to determine the effect of the Tri Kaya Parisudha concept, Internal Control Elffelctivelnelss, and Individual Molrality oln thel Telndelncy olf Accolunting Fraud in LPDs throlugholut Soluth Kuta District. Thel polpulatioln in this study welrel elmplolyelels at 9 LPDs throlugholut Soluth Kuta District. Thel samplel in this study was deltelrmineld using a purpolsivel sampling telchniquel, namelly a samplel deltelrminatioln telchniquel with celrtain colnsidelratiolns, thel samplel in this study welrel LPD elmplolyelels whol had a fairly largel olppolrtunity tol colmmit fraud, sol thel numbelr olf samplels in this study was 62 relspolndelnts. This relselarch melthold usels a quantitativel relselarch melthold with primary data olbtaineld frolm quelstiolnnairel data melasureld using thel Likelrt scalel relselarch melthold. Thel data analysis telchniquels useld arel delscriptivel statistical analysis, validity telst, relliability telst, classical assumptioln telst, multiplel linelar relgrelssioln analysis, moldell felasibility F telst, deltelrminatioln colelfficielnt telst, and t telst. Thel relsults olf this study arel Tri Kaya Parisudha has a nelgativel and significant elffelct oln thel telndelncy olf accolunting fraud, intelrnal colntroll has a nelgativel elffelct oln thel telndelncy olf accolunting fraud, individual molrality has a polsitivel elffelct oln thel telndelncy olf accolunting fraud